Magnetic nano-adsorbents applications and modelling for green environmental remediations / Muhammad Abdur Rehman - Muhammad , Abdur Rehman (2016)
This work describes some general procedures for the preparation, characterization of adsorbents, CuFe2O4, CuCe0.1Fe2O4, CuCe0.2Fe2O4, CuCe0.3Fe2O4, CuCe0.4Fe2O4, CuCe0.5Fe2O4, CuCe0.2Fe2O4-rGO, POCS (X=4.75), POCS (X=2.36), POCS (X=1.18), POCS (X=0.6), POCS (X=0.3), POCS (X=0.15) and their application for the decontamination of hydrological samples in an environment of high competitions for available active sites on the surface of adsorbents. A detailed characterization and analysis were carried out by the Fourier Transform Infrared spectroscopy (FTIR), Raman spectroscopy, X-ray Diffraction (XRD), BET surface area, particle size analyzer, Zeta Potential (ZP), Thermal gravimetric analysis (TGA & DTA), Field emission scanning electron microscopy (FESEM), Transmission Electron microscopy (TEM), Nuclear magnetic resonance (NMR), High performance liquid chromatography (HPLC), ion chromatography (IC), Inductively coupled mass spectroscopy (ICPMS), Electrochemical impedance spectroscopy (EIS), Linear scan cyclic voltammetry (LSCV) and UV-Visible spectroscopy that revealed the formation of impurity free magnetic adsorbents. The adsorbents were applied for the green environment remediation of heavy metals, anionic species and organophosphorus acephate. The properties of these synthetic adsorbents were fine-tuned by the facile process of doping rare earths, monitored by Autolab PGSTAT 302N and NOVA 1.10 software. Response surface methodology (RSM) for optimum adsorption and central composite design (CCD) was selected to study the main effects and interaction effects of various controlling parameter such as Adsorbent dose (g L-1), mixing speed (r/min), temperature (oC) and initial concentration (mgL-1). The nature of all the interaction was explained by a number of isotherms and kinetic models. Kinetic models include, pseudo first order, pseudo second order, Banghams, intra-particle diffusion, while the equilibrium models such as Langmuir, Freundlich, Temkin, Dubenin Redushkvich (DR), and Flory Huggins (FH). The equilibrium and kinetic models were tested for goodness of fit between the observed and model predicted adsorption capacities (Qe) to explain the interaction removal mechanisms. The results were further used to prepare adsorbents, characterize, apply and check for the best fit model that explains the adsorption process. The series of CuCexFe2-xO4 (x=0.0 to 0.5) retained magnetic properties for fluoride adsorption with coefficient values of X1(74.29), X2 (25.31), X3 (36.99) and X4 (8.31) respectively. The natural POCS displayed Arsenic adsorption coefficient X1(1.62), X2 (1.81), X3 (0.80) and X4 (3.10). The isotherms results of Acephate show the value of Qe (Langmuir), 11.23 mgg-1 or 10.67 mgg-1 at 293K and 313K respectively. The pseudo second order kinetic model give best fit to the results (R2 = 0.998), and the value of Qe (pseudo second order) were 12.427 mgg-1and 12.280 mgg-1 at 293K and 313 K respectively. The magnetic separations, dopant facilitated dispersions and graphene layers provided some novel series of energy efficient adsorbent. The design of experiments strategy with various statistical standards designs helps optimize the adsorption conduction with minimal number of experiments, reducing the cost and time of research and development in green environmental remediation.